ANALISIS FAKTOR INTERNAL DAN EKSTERNAL YANG BERPENGARUH TERHADAP AUDIT REPORT LAG - Yosua Martin Sutikno; P. Basuki Hadiprajitno (Diponegoro Journal of Accounting, 2015)
The purpose of this research is to analyze the factors that affect audit report lag of financial reports to the manufacturing companies listed on the Indonesia Stock Exchange. The examined factors of this research are size company, board independence, audit committee, auditor opinion, reputable company KAP, auditor change, and ownership concentration as the independent variable, while the audit report lag as the dependent variable.The sample consists of 598 companies listed in the Indonesia Stock Exchange (IDX) and submitted financial reports to Bapepam in the period 2010-2013. The data that was used in this research was secondary data and selected by using purposive sampling method. Model analysis using multiple linear regression analysis. Using the F-test to determine the effect of simultaneous between company characteristics and capital structure. Using t-test to examine the partial correlation of each independent variable on audit report lag.Based on analytical results shows that variable auditor opinion, reputable company KAP, and ownership concentration have significant influence toward audit report lag, while variable size company, board independence, audit committee and auditor change doesn’t have significant influence toward audit report lag.